Comparing the Effectiveness of Reality Therapy and Solution-Oriented Therapy on Academic Procrastination and Academic Hope of Female Secondary High School Students in Bandar Abbas City - Maryam Abolfathi; Ashraf Beirami; Moosa Javdan (Journal of Community Health Research)
Background: One of the most important effective factors in the discussion of motivation and academic progress can be found in the concepts of procrastination and academic hope. Therefore, the present study was conducted to compare the effectiveness of reality therapy and solution-oriented therapy on academic procrastination and academic hope of secondary school girls in Bandar Abbas City. Methods: The research was semi-experimental with a pre-test-post-test design with a control group. The statistical population of the study was made up of all the female students of the second level of secondary education Bandar Abbas in the academic year of 2023-2024. Using the random sampling method, 45 people were selected and randomly assigned to two experimental groups and a control group. The research tools were Rothbloom and Solomon's (1984) academic procrastination questionnaires and Campbell and Cowen's (2001) academic hope questionnaires. The data were analyzed using covariance analysis. Results: The results showed that there is a significant difference in academic procrastination (P < 0.01& F = 514/91)  and academic hope (P < 0.01& F = 184/61) between the subjects of the experimental and control groups in the post-exam and follow-up stages in favor of the two experimental groups; Also, the results of the Bonferroni test showed that the difference between reality therapy and solution-oriented variables in procrastination and academic hope is significant in favor of reality therapy. Conclusion: Both approaches, especially reality therapy, can be used to improve students' procrastination and academic hope and ultimately increase their academic progress.